FOSTERING STUDENTS’ PRESENTATION SKILL USING INFOGRAPHIC: THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN ENGLISH FOR SPECIFIC PURPOSES - Sukerti, Gusti Nyoman Ayu (Sanata Dharma University Yogyakarta, 2019)
Mastering English skill for students at a vocational institution of higher education is a mounting problem as the students are expected to develop practical English skills in specific disciplinary knowledge and internalize the attitudes and professional values. Implementation of project-based learning (PBL) in teaching speaking particularly the presentation skill can be seen as an alternative to cover both areas as it encourages students to develop higher critical thinking, enhances deep learning and motivates students to be independent learners with exceptional self-management. This article presents the results of the study on the impact of project-based learning on students’ speaking achievement particularly their presentation skills and students’ perceptions on the PBL stages. Participants were 19 fourth-semester students enrolled in a three-year undergraduate program in Electrical Engineering. The goal of this project was to drive students’ engagement in speaking activities and put students in the language-specific setting in which language was naturally used based on the project characteristics. This research employed mixed methods in which the quantitative data, i.e., pre-test and post-test were analyzed using SPSS statistic 21. The finding showed that the correlation coefficient (r) was 0,575. Based on the interpretation scale of correlation coefficient by Guilford (1965), the range of the correlation coefficients is between the range of 0,401-0,700 which means that the correlation is quite strong. Based on the result of analysis using SPSS statistics 21 with 95% level of confidence, it was revealed that -tcount < -ttable (-6.269 < -2,10092) and the significance value (pvalue) of 2-tailed was less than 0,05 (0,000 < 0,05). It can be concluded that H1 was accepted and H0 was rejected signifying that there was a significant effect of PBL implementation in improving students’ speaking achievement. In addition, this study also analyzed qualitative data collected from google form and focus group discussion to gain students’ perception towards the implementation of PBL using infographic. The results of online questionnaire revealed that students experienced deep and autonomous learning through the stages conducted in the project. They gained better understanding on grammar and vocabulary during peer review and showed positive attitude in designing infographics as they could revise the structure of their presentation while designing the infographics’ wireframes. Consequently, learning speaking through project-based learning using infographic helped to enhance students’ engagement to series of works within the projects and foster their collaborative and communicative skills while working together in groups. The results showed a significant effect of PBL on students’ presentation skills and improve soft skills compatible to workplace requirements. Considering the positive result of this study, PBL is recommended to be applied in teaching speaking for students in higher vocational education as it gives beneficial impact on students’ content learning and soft skills.DOI: doi.org/10.24071/ijiet.2019.030210